Effects of Spacing on Sentence Reading in Chinese - Oralova, Gaisha; Kuperman, Victor (Frontiers in Psychology, 2021)
Given that Chinese writing conventions lack inter-word spacing, understanding whether and how readers of Chinese segment regular unspaced Chinese writing into words is an important question for theories of reading. This study examined the processing outcomes of introducing spaces to written Chinese sentences in varying positions based on native speaker consensus. The measure of consensus for every character transition in our stimuli sentences was the percent of raters who placed a word boundary in that position. The eye movements of native readers of Chinese were recorded while they silently read original unspaced sentences and their experimentally manipulated counterparts for comprehension. We introduced two types of spaced sentences: one with spaces inserted at every probable word boundary (heavily spaced), and another with spaces placed only at highly probable word boundaries (lightly spaced). Linear mixed-effects regression models showed that heavily spaced sentences took identical time to read as unspaced ones despite the shortened fixation times on individual words (Experiment 1). On the other hand, reading times for lightly spaced sentences and words were shorter than those for unspaced ones (Experiment 2). Thus, spaces proved to be advantageous but only when introduced at highly probable word boundaries. We discuss methodological and theoretical implications of these findings.